(untitled) (Portuguese Journal of Family Medicine and General Practice, 2008)
Objective: To summarize, briefly, the risk of alcohol to health and what general practice can do to reduce the risk. Methodology: Two key texts previously written by the author were reviewed, and main points highlighted of the risks important to general practice and of the evidence that general practice can make a difference in reducing the risks. The two texts were updated following a recent Cochrane meta- -analysis of the impact of brief advice in reducing hazardous and harmful alcohol consumption. Conclusions: Alcohol increases the risk of a wide range of neuropsychiatric, gastrointestinal, endocrine, metabolic, and pre-natal conditions, as will increasing the risk of cancers and diseases of the cardiovascular system and impairing the immune system. Brief advice is effective in reducing hazardous and harmful alcohol consumption, with longer counselling providing little additional benefit. Ideally, an early identification (using the first three questions of the alcohol use disorders identification test (AUDIT)) and brief advice programmes should be offered to all adults, but, to begin with, screening programmes could be targeted at middle age men with chronic illness. The brief advice should consist of giving feedback, providing information, enabling a goal to be set, giving advice, and providing encouragement.